1990
DOI: 10.1016/0002-9149(90)90501-q
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative angiographic assessment of elastic recoil after percutaneous transluminal coronary angioplasty

Abstract: Little is known about the elastic behavior of the coronary vessel wall directly after percutaneous transluminal coronary angioplasty (PTCA). Minimal luminal cross-sectional areas of 151 successfully dilated lesions were studied in 136 patients during balloon inflation and directly after withdrawal of the balloon. The circumvent geometric assumptions about the shape of the stenosis after PTCA, a videodensitometric analysis technique was used for the assessment of vascular cross-sectional areas. Elastic recoil w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(37 citation statements)
references
References 19 publications
(1 reference statement)
1
33
1
2
Order By: Relevance
“…Percutaneous coronary intervention (PCI) remains a delicate balance between controlled mechanical disruption and the competing forces of elastic recoil, inflammation, and cell proliferation. 1,2 Although stents have essentially eliminated vessel reocclusion, restenosis has remained a costly and highly morbid problem. [3][4][5] Mechanical disruption of the endothelium and media appears to trigger intimal and vascular smooth muscle proliferation around the stent surface, and borrowing from the oncologic armamentarium, cell-cycle inhibition has been shown to inhibit this process.…”
Section: Resultsmentioning
confidence: 99%
“…Percutaneous coronary intervention (PCI) remains a delicate balance between controlled mechanical disruption and the competing forces of elastic recoil, inflammation, and cell proliferation. 1,2 Although stents have essentially eliminated vessel reocclusion, restenosis has remained a costly and highly morbid problem. [3][4][5] Mechanical disruption of the endothelium and media appears to trigger intimal and vascular smooth muscle proliferation around the stent surface, and borrowing from the oncologic armamentarium, cell-cycle inhibition has been shown to inhibit this process.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanisms involved in early loss are thought to be related to elastic recoil and/or dissection with or without intracoronary thrombosis [13,14]. The occurrence and the magnitude of early recoil may also depend on the specific mechanism of lumen gain and the quality of the residual vessel wall tissue rather than the final MLD alone [9,10,15].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in the coronary field have shown that a higher balloon/vessel ratio leads to a greater degree of elastic recoil 3,22 . Mummert et al 23 reported, in an experimental model, that aortic root compression forces were dependent on the amount of THV oversizing.…”
Section: Predictors Of Recoilmentioning
confidence: 99%